1993
DOI: 10.1161/01.atv.13.7.994
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness of aortic smooth muscle cells to soluble growth mediators is influenced by cell-matrix contact.

Abstract: Excessive proliferation and overexpresslon of collagens by smooth muscle cells (SMCs) are important features of atherogenesis. To understand the role of the extracellular matrix in the regulation of these processes, we examined proliferation and protein/collagen synthesis of SMCs in contact with a collagen matrix. Adult pig SMCs were isolated from the aortic media by collagenase digestion, subcultured as monolayers, and then embedded into a three-dimensional network of type I collagen, ie, a collagen lattice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Studies by Thie et al have demonstrated striking differences between VSMCs cultured on 2D plates vs. in a 3D collagen lattice. Thus, VSMCs have slower rates of collagen synthesis and cell proliferation in a 3D collagen lattice compared to the 2D monolayer (Thie et al, 1991(Thie et al, , 1993. The same investigators have found that the VSMCs isolated from both SHR and control normotensive rats have a lower protein synthesis rate in 3D culture than in 2D monolayers, but this 3D vs. 2D difference is lesser in the VSMCs from the SHR (Thie et al, 1992).…”
Section: D Vs 3d Cultures Of Vsmcsmentioning
confidence: 99%
“…Studies by Thie et al have demonstrated striking differences between VSMCs cultured on 2D plates vs. in a 3D collagen lattice. Thus, VSMCs have slower rates of collagen synthesis and cell proliferation in a 3D collagen lattice compared to the 2D monolayer (Thie et al, 1991(Thie et al, , 1993. The same investigators have found that the VSMCs isolated from both SHR and control normotensive rats have a lower protein synthesis rate in 3D culture than in 2D monolayers, but this 3D vs. 2D difference is lesser in the VSMCs from the SHR (Thie et al, 1992).…”
Section: D Vs 3d Cultures Of Vsmcsmentioning
confidence: 99%
“…Cells from an atherosclerotic vessel synthesize type 1 collagen in preference to type 3 collagen, unlike the cells of normal arteries [20][21][22]. Thie et al [5,6] reported that type 1 collagen inhibits proliferation of SMC. A contractile phenotype of SMC does not respond to serum mitogens [23].…”
Section: Discussionmentioning
confidence: 99%
“…These cells migrate from the media to the intima of the aorta and proliferate in response to growth factors such as platelet derived growth factor (PDGF) and basic-fibroblast growth factor (b-FGF) [4]. Type 1 collagen, which is abundant in the artery, inhibits the proliferation of SMC [5,6]. Recent studies postulate that excessive glycation of proteins is a cause of the vascular complications of diabetes.…”
mentioning
confidence: 99%
“…Second, while the codelivery of both growth factors eliminated the mitogenic response to either growth factor alone in 2D culture, this was not observed in 3D culture. While these discrepancies may be attributable to incomplete penetration of growth factors into the ECM altering effective growth factor concentrations, it is more likely due to cell/matrix/growth factor interactions which may modulate the growth factor response, either by altering cell signaling or cellular FGF or PDGF receptor expression and occupancy 47–50. Alterations in cellular phenotype by the 3D ECM conformation may also account for these changes, leading to differential expression of competence factors and cellular organelles, growth factors and growth factor and integrin receptors, and altered synthetic capacity in response to exogenous growth factor delivery 51.…”
Section: Discussionmentioning
confidence: 99%
“…While these discrepancies may be attributable to incomplete penetration of growth factors into the ECM altering effective growth factor concentrations, it is more likely due to cell/matrix/growth factor interactions which may modulate the growth factor response, either by altering cell signaling or cellular FGF or PDGF receptor expression and occupancy. [47][48][49][50] Alterations in cellular phenotype by the 3D ECM conformation may also account for these changes, leading to differential expression of competence factors and cellular organelles, growth factors and growth factor and integrin receptors, and altered synthetic capacity in response to exogenous growth factor delivery. 51 Stegemann had demonstrated that SMCs in 3D collagen matrices demonstrate less expression of a-SMA, a marker of the ''contractile'' SMC phenotype compared to cells cultured on a 2D collagen lattice.…”
Section: Discussionmentioning
confidence: 99%